Mobile Health Monitoring System using Fuzzy Logic - Rao, Naseem; Kumar, Anil; Abbasi, T. A. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
This paper was tested on a set of data in order to prove its effectiveness. Simulation gives promising results in detecting the activity of the person. This is efficient system for health monitoring as compare with conventional system. In this paper, to identify person’s activity fuzzy logic is used. It is found that this system is quick, easy to handle and robust in health monitoring.